Factors Affecting the Use of Long-Term Contraception - Aris Prastyoningsih; Anita Sri Sulistyowati; Juda Julia Kristiarini (GLOBAL HEALTH SCIENCE GROUP, 2023)
Indonesia's Total Fertility Rate is above the ASEAN average of 2.4 per 1000 Women of Reproductive Age and has continued to experience a stagnation period in the last 4 periods. In addition, the maternal mortality rate in Indonesia is still high at 359 per 100,000 live births. Long-Term Contraceptive Method is the most effective method of contraception to reduce birth rates but its users are only 20.3%. The national family planning program prioritizes the use of long-term contraceptive methods, but long-term contraceptive coverage is still low. This study aims to analyze the factors that influence the use of long-term contraception of the IUD type and implants at the Sang Timur Klaten Clinic. This type of research is quantitative research, with a research approach using a cross-sectional design with the research sample being couples of childbearing age using long-term contraception of the Implant and IUD type. The population in this study was 115 acceptors recorded in the register at the clinic. Non-random sampling technique used inclusion criteria. The inclusion criteria in this study are: Acceptors who are willing to be respondents, PUS who have followed long-term contraceptive methods. Data analysis with Chi-Square with a confidence level of 95%. The results of the bivariate analysis in this study used the Chi-Square test and the multivariate test used logistic regression. The results showed that there was a relationship between age, education and menstrual history with the use of long-term contraceptive methods with a p value <0.05. There is no relationship between work, parity, husband's support and family income with the use of long-term contraceptive methods with a p value > 0.05. The most dominant factor with long-term contraceptive use is education.